Smoking and survival of colorectal cancer patients: Population‐based study from Germany. Issue 6 (29th May 2015) - Walter, Viola; Jansen, Lina; Hoffmeister, Michael; Ulrich, Alexis; Chang‐Claude, Jenny; Brenner, Hermann
<x xml:space="preserve">Abstract</x> Current evidence on the association between smoking and colorectal cancer (CRC) prognosis after diagnosis is heterogeneous and few have investigated dose‐response effects or outcomes other than overall survival. Therefore, the association of smoking status and intensity with several prognostic outcomes was evaluated in a large population‐based cohort of CRC patients; 3, 130 patients with incident CRC, diagnosed between 2003 and 2010, were interviewed on sociodemographic factors, smoking behavior, medication and comorbidities. Tumor characteristics were collected from medical records. Vital status, recurrence and cause of death were documented for a median follow‐up time of 4.9 years. Using Cox proportional hazards regression, associations between smoking characteristics and overall, CRC‐specific, non‐CRC related, recurrence‐free and disease‐free survival were evaluated. Among stage I–III patients, being a smoker at diagnosis and smoking ≥15 cigarettes/day were associated with lower recurrence‐free (adjusted hazard ratios (aHR): 1.29; 95% confidence interval (CI): 0.93–1.79 and aHR: 1.31; 95%‐CI: 0.92–1.87) and disease‐free survival (aHR: 1.26; 95%‐CI: 0.95–1.67 and aHR: 1.29; 95%‐CI: 0.94–1.77). Smoking was associated with decreased survival in stage I–III smokers with pack years ≥20 (Overall survival: aHR: 1.40; 95%‐CI: 1.01–1.95), in colon cancer cases (Overall survival: aHR: 1.51; 95%‐CI: 1.05–2.17) and men (Recurrence‐free survival: aHR: 1.51; 95%‐CI: 1.09–2.10; disease‐free survival: aHR: 1.49; 95%‐CI: 1.12–1.97), whereas no associations were seen among women, stage IV or rectal cancer patients. The observed patterns support the existence of adverse effects of smoking on CRC prognosis among nonmetastatic CRC patients. The potential to enhance prognosis of CRC patients by promotion of smoking cessation, embedded in tertiary prevention programs warrants careful evaluation in future investigations.